THE IMPACT OF THE MASS MEDIA IN SHAPING PUBLIC OPINION ON GOVERNMENT POLICIES IN THE SOCIAL SERVICES AGENCY OF GOWA REGENCY - Nurjannah; Eka Fitra Ramadani; Hidayat, Iksan (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The mass media, as a means of providing information, plays an important role in disseminating issues that arise in society. More specifically, the mass media has the power to spread public opinion. This study aims to analyze the extent to which mass media exposure can influence the formation of public opinion regarding government policies in the Social Services Agency of Gowa Regency and to determine the extent to which public opinion influences the implementation of government policies in the Social Services Agency of Gowa Regency. This study uses a quantitative approach with a data collection technique, namely a questionnaire, administered to 100 respondents. The focus of this study is the extent to which mass media exposure can influence the formation of public opinion regarding government policies at the Social Services Agency. The data analysis techniques used in this study were simple linear regression, T-test (partial), F-test (simultaneous), and coefficient of determination. The results of the study show that, partially, the mass media has a positive and significant effect on public opinion, while public opinion has a negative effect on the implementation of government policies.